2015
DOI: 10.1136/jnnp-2015-310926
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus stimulation improves Parkinson's disease-associated camptocormia in parallel to its preoperative levodopa responsiveness

Abstract: STN stimulation improves PD-associated camptocormia in parallel with preoperative levodopa responsiveness. Long symptom duration interferes with levodopa responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 29 publications
2
38
0
3
Order By: Relevance
“…These three studies report comparisons of pre‐ and postsurgical means, but individual patient data are not available . Of the remaining 35 articles, there were three additional retrospective cohort studies, 12 case series with sample sizes of up to 25 patients, and 20 case reports …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These three studies report comparisons of pre‐ and postsurgical means, but individual patient data are not available . Of the remaining 35 articles, there were three additional retrospective cohort studies, 12 case series with sample sizes of up to 25 patients, and 20 case reports …”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐one studies evaluated the effects of DBS on postural deformities in PD patients. One study reported postural abnormalities after withdrawal of dopaminergic medications . The other 30 studies retrospectively analyzed postural deformities during the best medication and stimulation conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations